CAR ZAZ-1102 IMPROVEMENT IN FUEL EFFICIENCY AND ENVIRONMENTAL PERFORMANCE IN WARM-UP PHASE AFTER ENGINE COLD START - Gutarevich, Yu. F.; Trifonov, D. M; Syrota О. V. (Academic journal Industrial Machine Building Civil Engineering, 2017)
The article considers the question that relates to optimizing fuel consumption and reducing emissions of harmful substances in the exhaust gases of the vehicle in the following modes cold start of the engine with spark ignition and warm-up. To solve this problem device is proposed for increasing the temperature of the intake air at low temperatures, which will improve the mixture formation, gas exchange and better distribution of the fuel-air mixture in the engine cylinders. The use of this device is one of the promising directions of implementation of energy efficient technologies in road transport.